Activation of p90(Rsk1) Is Sufficient for Differentiation of PC12 Cells - Silverman, Eran (American Society for Microbiology, 2004)
We investigated the role of Rsk proteins in the nerve growth factor (NGF) signaling pathway in PC12 cells. When rat Rsk1 or murine Rsk2 proteins were transiently expressed, NGF treatment (100 ng/ml for 3 days) caused three- and fivefold increases in Rsk1 and Rsk2 activities, respectively. Increased activation of both wild-type Rsk proteins could be achieved by coexpression of a constitutively active (CA) mitogen-activated protein kinase (MAPK) kinase, MEK1-DD, which is known to cause differentiation of PC12 cells even in the absence of NGF. Rsk1 and Rsk2 mutated in the PDK1-binding site were not activated by either NGF or MEK1-DD. Expression of constitutively active Rsk1 or Rsk2 in PC12 cells resulted in highly active proteins whose levels of activity did not change either with NGF treatment or after coexpression with MEK1-DD. Rsk2-CA expression had no detectable effect on the cells. However, expression of Rsk1-CA led to differentiation of PC12 cells even in the absence of NGF, as evidenced by neurite outgrowth. Differentiation was not observed with a nonactive Rsk1-CA that was mutated in the PDK1-binding site. Expression of Rsk1-CA did not lead to activation of the endogenous MAPK pathway, indicating that Rsk1 is sufficient to induce neurite outgrowth and is the only target of MAPK required for this effect. Collectively, our data demonstrate a key role for Rsk1 in the differentiation process of PC12 cells.